Insulin-Regulated Aminopeptidase Inhibition Ameliorates Metabolism in Obese Zucker Rats - Krskova, Katarina; Balazova, Lucia; Dobrocsyova, Viktoria; Olszanecki, Rafal; Suski, Maciej; Chai, Siew Yeen; Zorad, Štefan (Frontiers in Molecular Biosciences, 2020)
The aim of our study was to determine the influence of inhibition of insulin-regulated aminopeptidase/oxytocinase (IRAP) on glucose tolerance and metabolism of skeletal muscle and visceral adipose tissue in obese Zucker rats. Obese Zucker rats administered with IRAP inhibitor–HFI-419 at a dose of 29µg/100g BW/day by osmotic minipumps implanted subcutaneously for 2 weeks. Two-hour intraperitoneal glucose tolerance test (ipGTT) was performed in fasting rats. Plasma oxytocin levels were measured by enzyme immunoassay after plasma extraction. In the musculus quadriceps and epididymal adipose tissue, the expression of factors affecting tissue oxidative status and metabolism was determined by real-time qPCR and/or Western blot analysys. The plasma and tissue enzymatic activities were determined by colourimetric or fluorometric method. Circulated oxytocin levels in obese animals strongly tended to increase after HFI-419 administration. This was accompanied by significantly improved glucose utilization during ipGTT and decreased area under the curve (AUC) for glucose. In skeletal muscle IRAP inhibitor treatment up-regulated enzymes of antioxidant defense system - superoxide dismutase 1 and 2 and improved insulin signal transduction pathway. HFI-419 increased skeletal muscle aminopeptidase A expression and activity and normalized its plasma levels in obese animals. In epididymal adipose tissue, gene expression of markers of inflammation and adipocyte hypertrophy was down-regulated in obese rats after HFI-419 treatment. Our results demonstrate that IRAP inhibition improves whole-body glucose tolerance in insulin-resistant Zucker fatty rats and that this metabolic effect of HFI-419 involves ameliorated redox balance in skeletal muscle.